Controlled Release of Cefixime using Sodium Carboxymethyl Cellulose Polymer - Kawther Abd Alwahid (Journal of Global Pharma Technology, 2018)
Environmentally benign and efficient route of synthesis of   PAA-g-SCMC was prepared via irradiation (800W) using modified household microwave alone (without using initiator). PAA-g-SCMC polymer before and after loading with the drug was confirmed on FT-IR spectrophotometer and SEM.   SCMC polymer was also used to extend the release of antibiotic namely, Cefixime.  Buffer solutions of pH 7.2 and 1.2 were used as the medium for the release of drug to simulate the pH media of small intestine and stomach respectively. We used UV-visible spectrophotometer fo imbibing measuring solution of antibiotic for Cefixime respectively at 285 nm. The antibiotic release was done at different temperature (25 ⁰C, 37⁰C). Generally, the release was   increased at pH 7.2 and temperature at 37⁰C. The results obtained from the grafted polymers were better than the non grafted polymers concerning the controlled release of the drug.Keywords: Cefixime; SCMC polymer; Buffer solutions; Deionized water (D.W); Grafted polymer PAA-g-SCMC.